PENGARUH JENIS DAN KEPADATAN IKAN TERHADAP PENGELOLAAN MATALELE (Azolla pinnata L. ) DAN HASIL PADI IR-64 SERTA HASIL IKAN PADA SISTEM MINAPADI THE INFLUENCE OF TYPE AND FISH DENSITY TO MATA LELE (Azolla pinnata L. ) MANAGEMENT AND IR-64 RICE RESULT AND - M. TH. Darini M. TH. Darini (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2010)
The purpose of research is to known type and exactly density fish to aquatic plant Azolla pinnata growth until to give the IR-64 rice result and the best fish, have done in fish nursery center, Wonocatur, Banguntapan, Bantul, Yogyakarta. Located at 112 m up sea level. Land type is Regosol, daily temperature average 28 0C. The research is field experiment that consist two factors, arranged in Randomized Completely Block Design, with three replicates. The first factor is type of fish (1), of two levels: Tawes fish (11) and Nila fish (12). The second factor is fish density per meter field sided (K), of three levels: there are no fish (KO), 1 fish (K 1), and 2 fishs (K2). The result of the research indicated influence between type and density fish to rice result. The Tawes fish with density 1 and 2 fishs per m2 field and Nila fish with density 2 fish per m2 field lave given the highest rice result. Tawes fish with 2 fishs per m2 field more impede Azolla pinnata L. Fish density 2 fishs per m2 field have given fish result higer. Fish weight average of 1 fish per m2 field Â higher than 2 fish per m2 field.